PENGARUH PERENDAMAN EKSTRAK BAWANG MERAH (ALLIUM CEPA L.) TERHADAP VIABILITAS BENIH KOPI ROBUSTA (COFFEA CANEPHORA) - I. K. Dita Adnyana; Mahfudz Mahfudz; Syamsiar Syamsiar (Fakultas Pertanian, Universitas Tadulako, 2022)
Coffee is one of Indonesia export commodity which is quite important as a source of foreign exchange. In an effort to increase coffee production, it must be started with the provision of quality seeds, affordable and available in sufficient quantities, where one of them is by generative propagation or using seeds, but the disadvantages of propagation using beans are the long dormancy period of coffee and low viability of coffee seeds when planted in the field so that additional treatment is needed before the seeds are germinated. This study aims to determine the best soaking concentration of shallot extract on the viability of robusta coffee seeds. The research method used a single factor randomized block design (RBD) with a treatment factor, namely the soaking concentration of shallot extract consisting of eight levels, namely K0 = 0%, K1 = 40%, K2 = 50%, K3 = 60%, K4 = 70% , K5 = 80%, K6 = 90% and K7 = 100%. This treatment was repeated 4 times so that there were 32 experimental units per unit experiment consisting of 20 seeds so that the seeds used were as many as 640 seeds, the data were analyzed by analysis of variance and 5% LSD test. The results showed that immersion of robusta coffee seeds with onion extract at a concentration of 50% resulted in a percentage of germination, synchronization of growth and a maximum growth potential of 95% and soaking of onion extract with a concentration of 100% resulted in high robusta coffee seeds reaching 10.96 cm and the root length of Robusta coffee seedlings reaches 7.43 cm.